Analisis Biaya Pemupukan pada Tanaman Belum Menghasilkan (TBM) Kelapa Sawit di Kebun Tanjung Garbus KSO PT. Perkebunan Nusantara IV Regional 2 - Walmadri, Walmadri; Maisarah, Maisarah; Khairad, Fastabiqul; Manurung, Saroha; Nasution, Taufiq Ridho Ibrahim (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
This study aims to analyze fertilization costs for immature oil palm (Elaeis guineensis Jacq.) at the Tanjung Garbus Plantation Afdeling 2, PT. Perkebunan Nusantara IV Regional 2 focuses on fertilizer, labor, and transportation costs. The method used is quantitative descriptive analysis, with secondary data collection from the company. The results show that the total fertilization cost in the 2018 planting year at Afdeling 2 amounted to IDR 1,353,060,492. The breakdown of costs includes fertilizer purchases amounting to IDR 1,304,734,345, transportation costs of IDR 6,026,147, and labor costs of IDR 256,643. The fertilization cost per hectare in the 2018 planting year is IDR 1,353,060,492. The largest proportion of the total cost is fertilizer costs, which account for 96% of the total fertilization operation cost. This study provides a clear overview of cost allocation in oil palm fertilization during the immature stage (TBM).